2013
DOI: 10.1097/ccm.0b013e3182a16898
|View full text |Cite
|
Sign up to set email alerts
|

Benzodiazepine Versus Nonbenzodiazepine-Based Sedation for Mechanically Ventilated, Critically Ill Adults

Abstract: Current controlled data suggest that use of a dexmedetomidine- or propofol-based sedation regimen rather than a benzodiazepine-based sedation regimen in critically ill adults may reduce ICU length of stay and duration of mechanical ventilation. Larger controlled studies are needed to further define the impact of nonbenzodiazepine sedative regimens on delirium and short-term mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
148
1
7

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 255 publications
(175 citation statements)
references
References 40 publications
9
148
1
7
Order By: Relevance
“…Several reasons may explain the difference in findings on mortality between our study and the meta-analysis by Fraser et al [3]. One possibility is the fundamental difference in data source: while the meta-analysis involved pooled data from six papers, our study used a multi-center database.…”
Section: Abstract Propofol · Benzodiazepines · Mechanical Ventilationmentioning
confidence: 74%
“…Several reasons may explain the difference in findings on mortality between our study and the meta-analysis by Fraser et al [3]. One possibility is the fundamental difference in data source: while the meta-analysis involved pooled data from six papers, our study used a multi-center database.…”
Section: Abstract Propofol · Benzodiazepines · Mechanical Ventilationmentioning
confidence: 74%
“…3 The choice of the ideal sedative agent is difficult, and must take into account the pharmacology of the drugs and the different pathologies. New studies have shown that the use of benzodiazepines leads to a longer need for ventilatory support (1.9 days, p<0.00001) and longer ICU length of stay (1.65 days, p=0.0005), as demonstrated by a review and meta-analysis by Fraser et al 29,39 Also, it was shown that the prevalence of delirium, in the use of nonbenzodiazepine agents, is lower, implicating in smaller hospitalization cost. 29,40 Recently, the preferential use of non-benzodiazepine sedatives, such as dexmedetomidine and propofol, has been advocated based on the Pain, Agitation and Delirium (PAD) guidelines for adult patients.…”
Section: Resultsmentioning
confidence: 98%
“…A recent meta-analysis by Fraser and colleagues [2] also compared these sedation strategies and demonstrated similar results. However, the latter did not demonstrate a significant difference in mortality.…”
Section: Abstract Sedation · Propofol · Benzodiazepines · Mechanical mentioning
confidence: 84%